MBV: a method to solve sample mislabeling and detect technical bias in large combined genotype and sequencing assay datasets - Alexandre Fort; Nikolaos Panousis; Marco Garieri; Stylianos E. Antonarakis; Tuuli Lappalainen; Emmanouil T. Dermitzakis; Olivier Delaneau (2017)
Large genomic datasets combining genotype and sequence data, such as for expression quantitative trait loci (eQTL) detection, require perfect matching between both data types.We described here MBV (Match BAM to VCF); a method to quickly solve sample mislabeling and detect cross-sample contamination and PCR amplification bias.MBV is implemented in C ++ as an independent component of the QTLtools software package, the binary and source codes are freely available at https://qtltools.github.io/qtltools/ .olivier.delaneau@unige.ch or emmanouil.dermitzakis@unige.ch.Supplementary data are available at Bioinformatics online.